1998
DOI: 10.1109/20.706587
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low inductance thin-film single-pole head on flying slider

Abstract: A novel single-pole head on a flying slider is presented as a high frequency writing head. The main pole of the head is driven with three thin-film conductor layers to have a short magnetic circuit path. Thus, a low inductance of around 10 nH and a high writing sensitivity o f less than 0.03 AT,, is obtained. The writing field distribution is shown to be the same as a regular single-pole head by computer simulations. The recording performance of the head is examined and the high writing sensitivity is demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Fig. 5 shows magnetization loops along easy and hard axes of magnetization for films fabricated by stacking layer structure The stacking film of was used to the fabrication of SPT recording head [4] for perpendicular recording. A conventional head structure [6] was introduced to this demonstration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 5 shows magnetization loops along easy and hard axes of magnetization for films fabricated by stacking layer structure The stacking film of was used to the fabrication of SPT recording head [4] for perpendicular recording. A conventional head structure [6] was introduced to this demonstration.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a single-pole-type (SPT) recording head [4] for perpendicular media was fabricated using the FeCo films, and demonstrated that such films are sufficiently soft to be used for recording head applications. Manuscript II.…”
Section: Introductionmentioning
confidence: 99%